2018
DOI: 10.1017/s0954394518000169
|View full text |Cite|
|
Sign up to set email alerts
|

Segregated vowels: Language variation and dialect features among Gothenburg youth

Abstract: This paper examines the effects of housing segregation on variation in the vowel systems of young speakers of Swedish who have grown up in different neighborhoods of Gothenburg. Significant differences are found for variants of the variables /i:/ and /y:/, which are strongly associated with the local dialect; these two vowels also exhibit coherence. Another vowel pair, /ε:/ and /ø:/, are involved in a coherent leveling process affecting many of the central Swedish dialects but differing in degree of openness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Furthermore, the word rejeki is used to explain the singer's strong need for money for economic reasons. This is in line with the argument of (Adegoke, 2011;Gross, 2018;Hovy, 2015) that the economy becomes one of the factors influencing language use, and in this case, economic reasons influence the singers to use the word "usaha" which emphasizes his intention of working.…”
Section: Social Factors Representing Tkw's Lifesupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the word rejeki is used to explain the singer's strong need for money for economic reasons. This is in line with the argument of (Adegoke, 2011;Gross, 2018;Hovy, 2015) that the economy becomes one of the factors influencing language use, and in this case, economic reasons influence the singers to use the word "usaha" which emphasizes his intention of working.…”
Section: Social Factors Representing Tkw's Lifesupporting
confidence: 85%
“…Language use that aims to express feeling, emotion, condition, and identity is influenced by multiple factors, including age, social issues, economy, culture, ethnic, politic, education, gender, demography (Adegoke, 2011;Gross, 2018;Hovy, 2015), genre, key rules of interaction, aims, and norms (Salzmann et al, 2012;Wee, 2014). Furthermore, language use depends on its users' emotions because it determines the purposes and context of their communication (Adegoke, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of speakers for this study was done in two steps as an initial analysis 1 showed that the speakers in the north-eastern suburbs differed from the rest of the speakers in terms of the patterning of the two vowels of interest here: the suburban school was disregarded in the first step; speakers attending the city centre school but living in the north-eastern suburbs were excluded from the original data set in the second step (Gross, 2018). This selection was used to keep as many factors as possible constant.…”
Section: Methods and Datamentioning
confidence: 99%
“…This initial analysis contained examples of all of the long vowel tokens in Swedish (apart from /e:/ and /o:/): /i: y: ʉ: ɛ: ø: ɑ: u:/, plus the pre-rhotic allophones [ae: oe:]. 5,184 vowels were analysed, and the analysis is presented in more detail in Gross (2018).…”
Section: Phonemementioning
confidence: 99%
“…Results indicate that the lects labeled by linguists and laymen seem not to be realized in actual language use, and they should thus be reconsidered. The issue of lectal coherence (Guy, 2013) has been examined by focusing on patterns of covariation instead of singular variables (e.g., Gross, 2018;Oushiro, 2016).The sociolinguistic research on covariation patterns was introduced in Labov's study of English in New York City (Labov, 1966:209-11). The study presented two approaches to stratification of linguistic data: social grouping and linguistic grouping.…”
mentioning
confidence: 99%